PENERAPAN STRATEGI PEMBELAJARAN ACTIVE KNOWLEDGE SHARING UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KOLOID DI KELAS XI SMAN 1 KAMPAR TIMUR - Sepra Pajar; Betty Holiwarni; Sri Haryati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The purpose of this research to improve student achievement on the subject of colloid in class XI SMAN 1 Kampar Timur. Form of research is experiment research with pretest-posttest design. The sample consisted of two classes. Experiment class was given implementing learning strategies Active Knowledge Sharing, while the control class wasnot given implementing active learning strategies Active Knowledge Sharing. The t-test is used for data analysis technique. Based on the final results of data processing using t-test formula with dk=61 and ɑ=0,05 obtained Tarithmetic>Ttable (2.48>1.67) means that the application of learning strategies Active Knowledge Sharing can improve student achievement on the subject of colloid in class XI SMAN 1 Kampar Timur. Imporoved learning achievement because application of learning strategies active knowledge sharing thre student sued plays an active role in the learning process. Student can be seen from the liveliness of the willingness and aenthusiasm of the student in doing is student worksheet,discussion and knowledge sharing in problem solving with a group of friends or ather groups. Category Increased student achievement on experiment class including moderate with the normalized gain scores (N-gain) about 0,69.Keywords: Active Knowledge Sharing, Learning Achievement, Colloid